Effect of restricted feeding on the growth and body composition of European seabass Dicentrarchus labrax (Linnaeus, 1758) - Baki, Birol; Kaya Ozturk, Dilara; Sariipek, Merve; Kerim, Murat; Eyuboglu, Bora (Indian Journal of Fisheries, 2016)
The aim of this study was to determine the effects of restricted feeding on the growth and body composition in juvenile European seabass Dicentrarchus labrax, (Linnaeus, 1758). Four different feeding regimes were tested in fishes having average weight of 6.57±0.09 g. The three treatment groups were fed three times a day adopting three different regimes: 6 days feeding/1 day starvation (6F/1S), 5 days feeding/2 days starvation (5F/2S) and 4 days feeding/3 days starvation (4F/3S) for a period of 60 days. Control group (C) was fed daily three times a day. At the end of the study the average weights were 31.21±1.39 g (C), 36.47±1.33 g (6F/1S), 29.01±1.01 g (5F/2S) and 24.21±0.82 g (4F/3S) respectively (p